2021
DOI: 10.31234/osf.io/erzvp
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ROC asymmetry is not diagnostic of unequal residual variance in Gaussian signal detection theory

Abstract: Signal detection theory (SDT) is used to analyze yes/no judgment accuracy in many research domains of psychology. SDT yields separate estimates for response bias/criterion (c) and for sensitivity/discriminability (d'). Discrimination performance can be displayed in Receiver Operating Characteristics (ROCs) plotting hit and false alarm rates at various levels of confidence. We provide formal proof and simulations showing that asymmetric ROCs in Gaussian SDT are not exclusively diagnostic of unequal residual var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…It also stands that changes in the shape of the z-ROC are not exclusively caused by mnemonic factors (Malmberg & Xu, 2006;Rabe, Lindsay & Kliegl, 2021), and many models reflect this. For instance, previous models have added variability to recognition decision criteria, and have potential to add to discussion about the unequal variance assumption (Benjamin, Diaz, & Wee, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also stands that changes in the shape of the z-ROC are not exclusively caused by mnemonic factors (Malmberg & Xu, 2006;Rabe, Lindsay & Kliegl, 2021), and many models reflect this. For instance, previous models have added variability to recognition decision criteria, and have potential to add to discussion about the unequal variance assumption (Benjamin, Diaz, & Wee, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly found that z-ROCs calculated from recognition confidence data are approximately linear, with slopes less than 1 (Glanzer, Kim, Hilford, & Adams, 1999). Since the value of the z-ROC slope has long been presumed to represent the ratio σo / σn in a traditional Gaussian signal detection model (but see Rabe, Lindsay & Kliegl, 2021), a non-unit z-ROC slope necessitates making σo a free parameter with a value typically greater than σn. With this parameterization, the unequal variance signal detection (UVSD) model is defined as having parameters θ = {d, σo, C1, C2, … CI} where I is the highest decision criterion level in terms of strength (Kellen, Klauer, & Bröder, 2013).…”
mentioning
confidence: 99%